The story battle in the Ukraine war: From televised speeches to video selfies - Martín Sáez, José Luis; Ortiz de Guinea Ayala, Yolanda (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
History has shown that conflicts are not only waged on the ground in various theatres of operations, but also in a symbolical manner too, those scenarios where non-conventional combat strategies are used to win, in this case, the battle of the story. This is notable in a technological and communicative context, defined by hyper connectivity. In this context, we have made a narrative analysis of the war stories between Russia and Ukraine, based on the speeches of their respective presidents, to conclude that the two leaders have built an emotional story, using storytelling techniques.